Current issues in tropical phenology: a synthesis - Abernethy, Katharine; Bush, Emma R.; Forget, Pierre-Michel; Mendoza, Irene [UNESP]; Morellato, Leonor Patrícia Cerdeira [UNESP] (Wiley, 2018)
We retrace the development of tropical phenology research, compare temperate phenology study to that in the tropics and highlight the advances currently being made in this flourishing discipline. The synthesis draws attention to how fundamentally different tropical phenology data can be to temperate data. Tropical plants lack a phase of winter dormancy and may grow and reproduce continually. Seasonal patterns in environmental parameters, such as rainfall, irradiance or temperature, do not necessarily coincide temporally, as they do in temperate climes. We review recent research on the drivers of phenophase cycles in individual trees, species and communities and highlight how significant innovations in biometric tools and approaches are being driven by the need to deal with circular data, the complexity of defining tropical seasons and the myriad growth and reproductive strategies used by tropical plants. We discuss how important the use of leaf phenology (or remotely-sensed proxies of leaf phenophases) has become in tracking biome responses to climate change at the continental level and how important the phenophase of forests can be in determining local weather conditions. We also highlight how powerful analyses of plant responses are hampered at many tropical sites by a lack of contextual data on local environmental conditions. We conclude by arguing that there is a clear global benefit in increasing long term tropical phenology data collection and improving empirical collection of local climate measures, contemporary to the phenology data. Directing more resources to research in this sector will be widely beneficial.
Keywords: climate change; ecosystem change; tropical phenology